Essentials of maternity, newborn, and women's health nursing - Ricci, Susan Scott (Philadelphia : Wolters Kluwer, 2017)
"Since the health care focus of women and their families has expanded well beyond our nation's borders, more cultural and global aspects of maternity and women's health care have been added to this fourth edition. The United States is part of the international community, and as such nurses must understand and respect diverse cultures and their customs to truly play an important role as a global partner. Nurses care for a variety of women from many continents, thus they have to be armed with appropriate tools to meet their client's diverse needs. Also more evidence-based research findings have been included in this fourth edition for nurses to validate their practice and interventions"--
Perspectives on maternal, newborn, and women's health care -- Family-centered community-based care -- Anatomy and physiology of the reproductive system -- Common reproductive issues -- Sexually transmitted infections -- Disorders of the breasts -- Benign disorders of the female reproductive tract -- Cancers of the female reproductive tract -- Violence and abuse -- Fetal development and genetics -- Maternal adaptation during pregnancy -- Nursing management during pregnancy -- Labor and birth process -- Nursing management during labor and birth -- Postpartum adaptations -- Nursing management during the postpartum period -- Newborn transitioning -- Nursing management of the newborn -- Nursing management of pregnancy at risk : pregnancy-related complications -- Nursing management of the pregnancy at risk : selected health conditions and vulnerable populations -- Nursing management of labor and birth at risk -- Nursing management of the postpartum woman at risk -- Nursing care of the newborn with special needs -- Nursing management of the newborn at risk : acquired and congenital newborn conditions.
Includes bibliographical references and index.
Keywords: Maternity nursing; Gynecologic nursing; Maternal-Child Nursing; Obstetric Nursing; Pregnancy Complications -- nursing